Estudio de la agenda Setting que manejan los canales de televisión de la ciudad de Loja y su incidencia en la producción de noticias para la generación de una propuesta económica , periodo julio-diciembre de 2013 - Aguilar Moreno, Juan Pablo (2015)
Agenda setting, constitutes a tool that allows media to capture a series of strategies, ie make a plan to find and cover information to be disseminated to the community, taking into consideration these general allegations in the present research the following research question was formulated: The media of the city of Loja Uv TV and TV Ecotel not prepare their journalistic agenda based on common interests, thus preventing keep audiences informed, according to a schedule public. For this problem I had to make a direct observation of information transmitted by local channels daily for six months, so that he could determine the lack of planning that adequately sort the information content and thus to identify journalists' sources. Ecotel UV Television and TV, where media has focused the study, seek to build their own agenda, in order to achieve rating or at least remain at a good level. In this context to give meaning to the scientific logic, inductive, deductive methods was used; and technical survey and interview key tools that allowed to make a deep exploration of the problem, ie from an overall look to reach specific issues, determining causes, circumstances and reasons why the media do not handle public agenda. Finally it offers a proposal, the same will constitute an important contribution to the television media of the town, in order to achieve resolve their deficiencies in organization and planning information. Keywords: Agenda Setting. Media. News Production. Media Agenda